2003
DOI: 10.1159/000072452
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant <i>Mycobacterium tuberculosis</i>and <i>Aspergillus niger</i> Infection in a Patient with Acute Myeloid Leukemia

Abstract: Primary cutaneous infection by Aspergillus spp. is an uncommon form of aspergillosis in patients with severe immunosuppression, e.g. patients with HIV infection or hematological malignancies. Disruption of the dermal integrity by trauma or maceration, followed by colonization of the wound by Aspergillus spp. creates a suitable environment for cutaneous infection. Despite aggressive therapy with amphotericin, primary cutaneous aspergillosis can lead to disseminated disease with fatal consequences. Tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…TB may present with DIC and should be considered in the differential diagnosis of thrombocytopenia particularly in patients having abnormal chest radiographs [ 13 , 19 , 27 ]. In immunocompromised patients, TB may coexist with fungal infections and may be localized or disseminated [ 19 , 28 ]. Even in apparently healthy individuals living in endemic areas, TB is the commonest infectious cause of pyrexia of unknown origin [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TB may present with DIC and should be considered in the differential diagnosis of thrombocytopenia particularly in patients having abnormal chest radiographs [ 13 , 19 , 27 ]. In immunocompromised patients, TB may coexist with fungal infections and may be localized or disseminated [ 19 , 28 ]. Even in apparently healthy individuals living in endemic areas, TB is the commonest infectious cause of pyrexia of unknown origin [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 85 ] Compared to other species, A ustus was significantly associated with greater mortality (80%, P = 0.0341). Particularly in immunocompromised patients, it was not unusual to have concomitant infections such as concurrent dissemination ( Mycobacterium tuberculosis , [ 8 ] Escherichia coli and Pneumocystis jirovecii , [ 36 ] cytomegalovirus, [ 40 ] and Mycobacterium avium complex), [ 56 ] localized PCA during dissemination of other pathogens ( M avium complex, [ 40 ] Pseudomonas aeruginosa , and cytomegalovirus), [ 77 ] and localized coinfection ( Staphylococcus capitis ). [ 12 ]…”
Section: Resultsmentioning
confidence: 99%
“…In two cases, dissemination was reported at multiple organ sites: lungs, pericardium, stomach, liver, thyroid, gland, and brain in one patient; [ 41 ] and lung, spleen, and mesentery in the other. [ 62 ] In individual cases, there were reports of dissemination to the bone marrow [ 8 ] and kidney. [ 50 ] The time to dissemination (time from initial PCA diagnosis to diagnosis of dissemination) was reported in 10 of 22 cases (45.5%) and varied widely with a range of 3 to 120 days.…”
Section: Resultsmentioning
confidence: 99%
“…The three cases presented in our study comprise the first PCA series reported in immunocompetent adults in Turkey. Apart from these, the PCA cases previously reported from Turkey involved four immunosuppressed patients and one infant [16][17][18][19]. In order to differentiate PCA from other fungal pathologies and etiologies during diagnosis, obtaining tissue samples by biopsy for culture and histopathological examination is recommended [2].…”
Section: Discussionmentioning
confidence: 99%